Sintesis del conocimiento taxonomico, origen y domesticacion del genero Capsicum - Hernandez Verdugo, S.=700 1 Davila Aranda, P; Oyama, K.
(Es, En)
Ilus., 82 ref.
Keywords: TAXONOMIA; CAPSICUM; PROCEDENCIA; MEXICO; DOMESTICACION; CHILE